SURG-10. SPECTROSCOPIC MEASUREMENT OF 5-ALA-INDUCED INTRACELLULAR PROTOPORPHYRIN IX IN PEDIATRIC BRAIN TUMORS. (4th December 2020) - Schwake, Michael; Kaneko, Sadahiro; Morina, Eric Suero; Stummer, Walter
Abstract: OBJECTIVE: 5-ALA guided resection of glioma in adults enables better delineation between tumor and normal brain, allowing improved resection and improved patients' outcome. Recently, several reports were published regarding 5-ALA for resection of pediatric brain tumors. The aim of the study was to determine the intracellular fluorescence of PPIX in pediatric brain tumors by hyperspectral imaging and to compare it with visually observed intraoperative fluorescence. METHODS: 5-ALA was administered orally four hours prior to surgery. During tumor resection the surgeon assessed the fluorescence signal to be strong, weak or absent. Subsequently, fluorescence intensity of samples was measured via spectroscopy. In addition, clinical data, imaging and laboratory data were analyzed. RESULTS: Eleven children (1–16 years) were operated. Tumor entities included: three medulloblastomas, two pilocytic astrocytomas (PA), two anaplastic ependymomas and one diffuse astrocytoma, anaplastic astrocytoma, pilomyxoid astrocytoma and anaplastic pleomorphic xanthoastrocytoma. Strong fluorescence was visible in all anaplastic tumors and one PA; one PA demonstrated weak fluorescence. Visible fluorescence was strongly associated with intracellular fluorescence intensity and PPIX concentration (P<0.05). Within all tumors with visible fluorescence the intracellular PPIX concentration was greater than 4 µg/ml. Except for moderate and transient elevation of liver enzymes, no 5-ALA related adverse events were reported. CONCLUSION: We demonstrate a strong association between intraoperative observations and spectrometric measurements of PPIX fluorescence in tumor tissue. As in former studies, fluorescence signal was more commonly observed in malignant glial tumors. Further prospective controlled trials should be conducted to investigate the feasibility of 5-ALA guided resection of pediatric brain tumors.